203k views
5 votes
How to get the right answer

How to get the right answer-example-1
User Jeff Caros
by
5.8k points

2 Answers

1 vote

Answer:

yo, not that its any of my buisness but I feel like you should wipe your screen.

Step-but you should y-step explanation:

User Merab
by
6.1k points
4 votes

Plug the values for a, b, and c in the expression given.


(1)/(7)[(16)/(-4)+8(3-√(25))^(2)]=(1)/(7)[(16)/(-4)+8(3-5)^(2)]=(1)/(7)[-4+8(-2)^(2)]= (1)/(7)[-4+8(4)]=(1)/(7){[-4+32]=(1)/(7)[28]=4

User Ferdau
by
6.1k points